Pulmonary Vascular Morphology Associated With Gas Exchange in Systemic Sclerosis Without Lung Fibrosis. Issue 6 (November 2019) - Zhai, Zhiwei; Staring, Marius; Ninaber, Maarten K.; Vries-Bouwstra, Jeska K. de; Schouffoer, Anne A.; Kroft, Lucia J.; Stolk, Jan; Stoel, Berend C.
Abstract : Purpose: Gas exchange in systemic sclerosis (SSc) is known to be affected by fibrotic changes in the pulmonary parenchyma. However, SSc patients without detectable fibrosis can still have impaired gas transfer. We aim to investigate whether pulmonary vascular changes could partly explain a reduction in gas transfer of SSc patients without fibrosis. Materials and Methods: We selected 77 patients whose visual computed tomography (CT) scoring showed no fibrosis. Pulmonary vessels were detected automatically in CT images, and their local radii were calculated. The frequency of occurrence for each radius was calculated, and, from this radius histogram, 2 imaging biomarkers (α and β) were extracted, wherein α reflects the relative contribution of small vessels compared with large vessels, and β represents the vessel tree capacity. Correlations between imaging biomarkers and gas transfer [single-breath diffusion capacity for carbon monoxide corrected for hemoglobin concentration (DLCOc) %predicted] were evaluated with Spearman correlation. Multivariable stepwise linear regression was performed with DLCOc %predicted as the dependent variable and age, BMI, sPAP, FEV1 %predicted, TLC %predicted, FVC %predicted, α, β, voxel size, and CT-derived lung volume as independent variables. Results: Both α and β were significantly correlated with gas transfer ( R =−0.29, P -value=0.011 and R =0.32, P -value=0.004, respectively). The multivariable stepwise linear regression analysis selected sPAP [coefficient=−0.78; 95% confidence interval (CI)=−1.07, −0.49; P -value<0.001], β (coefficient=8.6; 95% CI=4.07, 13.1; P -value<0.001), and FEV1% predicted (coefficient=0.3; 95% CI=0.12, 0.48; P -value=0.001) as significant independent predictors of DLCOc %predicted ( R =0.71, P -value<0.001). Conclusions: In SSc patients without detectable pulmonary fibrosis, impaired gas exchange is associated with alterations in pulmonary vascular morphology. Abstract : Supplemental Digital Content is available in the text.